Synthesis of Bi2WO6 photoanode on transparent conducting oxide substrate with low onset potential for solar water splitting - Chae, Sang Youn; Lee, Eun Seon; Jung, Hyejin; Hwang, Yun Jeong; Joo, Oh-Shim (ROYAL SOC CHEMISTRY, 2014)
To enable water splitting in photoelectrochemical cells, the conduction-band (CB) and valence-band edges must straddle the hydrogenreduction and water-oxidation potentials; however, the CB edge potential of many photoanodic semiconductors is insufficient. Here, we demonstrate the nanostructured Bi2WO6 for photoanodic application, which has a high, flat-band potential of 0.15 V vs. RHE. Single-phase, orthorhombic Bi2WO6 nano-structures were successfully grown on an FTO substrate through a two-step hydrothermal synthesis with subsequent thermal treatment at 600 degrees C. The synthesized Bi2WO6 photoanode shows a lower onset potential and improved photocurrents which were enhanced further by a factor of three by coating the surface with Co-Pi. The low onset potential of the Bi2WO6/Co-Pi photoanode results in a higher operating photocurrent in a p/n photodiode cell combined with a p-Si/n-Si/Pt photocathode.
Keywords: PHOTOELECTROCHEMICAL HYDROGEN-PRODUCTION; OXIDATION; FILMS; CELLS; WO3; PHOTOCATALYSTS; EVOLUTION; NANORODS; PROGRESS; SYSTEM